Technical-Scientific Article - Atmospheric decarbonization and edible biomass production, a viable alternative - Modesto, Luis Antonio (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
This article explores the potential of biological carbon dioxide (CO₂) absorption by photosynthetic organisms — including algae, cyanobacteria, and higher plants — as a sustainable strategy for atmospheric decarbonization. It discusses the biochemical mechanisms underlying carbon fixation, the design and operation of controlled-scale cultivation systems (such as algal bioreactors), and provides preliminary calculations of CO₂ sequestration and oxygen generation. Furthermore, it examines the economic feasibility, implementation costs, optimal production conditions, and essential safety protocols associated with these systems. The study highlights the promise of integrating edible biomass production with environmental purification, positioning photosynthetic cultivation as a viable, scalable solution for reducing atmospheric CO₂ levels while contributing to food sustainability.